2022
DOI: 10.3389/fneur.2022.895527
|View full text |Cite
|
Sign up to set email alerts
|

Prospects and Dilemmas of Endovascular Treatment for Vertebrobasilar Dolichoectasia

Abstract: Vertebrobasilar dolichoectasia (VBD) is characterized by significant expansion, elongation, and tortuosity of the basilar artery and vertebral artery. Certain highly selected cases of VBD can require intervention. Recent advances in endovascular treatment (EVT) have renewed hope for patients with VBD. However, which cases of VBD can benefit from EVT still needs to be determined. Currently, little is known regarding this matter. Therefore, we performed a review of the literature from a PubMed search and catalog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 67 publications
(148 reference statements)
0
16
0
Order By: Relevance
“…Vertebrobasilar dolichoectasia (VBD) is vascular anomaly of dilation, elongation, increased length, diameter, and/or tortuosity of basilar and vertebral artery. 1 It comprised up to 80% of intracranial arterial dolichoectasia. 2,3 It is discovered incidentally in 1.3-4.4% of general population and symptomatically in 7.6-18.8% of stroke population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vertebrobasilar dolichoectasia (VBD) is vascular anomaly of dilation, elongation, increased length, diameter, and/or tortuosity of basilar and vertebral artery. 1 It comprised up to 80% of intracranial arterial dolichoectasia. 2,3 It is discovered incidentally in 1.3-4.4% of general population and symptomatically in 7.6-18.8% of stroke population.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 While it may be asymptomatic, VBD may manifest in 46.8% subjects as vascular or compressive symptoms, including ischemic stroke, and subarachnoid hemorrhage, cranial nerve compression, brainstem compression, hydrocephalus, cerebellar dysfunction, and central sleep apnea. 1,4 Wolters et al studied 375 VBD subjects and reported that the 5-year new event included ischemic stroke (17.6%), brainstem compression (10.3%), transient ischemic attack (10.1%), spontaneous intracerebral hemorrhage (4.7%), hydrocephalus (3.3%), and subarachnoid hemorrhage (2.6%). Another study by Passero and Rossi (2008) reported that of 156 subjects with VBD and median follow-up of 11.7 years, 43% had progression of VBD and approximately 60% experienced at least one symptomatic event.…”
Section: Introductionmentioning
confidence: 99%
“…Vertebrobasilar dolichoectasia (VBD) is defined as a marked dilation, extension, distortion, or angulation of the vertebrobasilar artery caused by various factors. Its prevalence in patients with stroke ranges from 7.6% to 18.8% [ 1 ]. Ischemic stroke (IS) is the most common clinical manifestation of VBD, followed by progressive compression of the cranial nerves and brainstem, cerebral hemorrhage, and hydrocephalus [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of its causes is the degeneration of the internal elastic lamina caused by arteriosclerosis or other unexplained conditions (1,2). The incidence rate of dolichoectasia is 1.3-4.4%, and the relevant factors of dolichoectasia are atherosclerosis, hypertension, age, smoking, and connective tissue diseases (3)(4)(5). Dolichoectasia is more likely to occur in large vessels such as the vertebrobasilar artery and internal carotid artery (ICA) and is less commonly observed in branch arteries (6,7).…”
Section: Introductionmentioning
confidence: 99%